Students' perception of the quality of teaching and learning in business studies programs - Abdul Hamid, Jamaliah; Lope Pihie, Zaidatol Akmaliah (Universiti Putra Malaysia Press, 2004)
A study was conducted to examine students' perceptions of the effectiveness of teaching and learning in business studies programs in their universities. About 1552 students enrolled as full time students in three public universities in Malaysia participated in the study. Three factors were employed to measure students' perceptions of effective teaching and learning. The factors were Lecturers' Factor, Teaching Methodology, and Course Relevance. Findings showed that a majority of respondents moderately agreed that their lecturers possessed and exhibited qualities described in all three constructs. Individual item description highlighted some interesting trends discussed in this paper. T tests and ANOVA showed significant differences in students' perceptions of all three factors based on their gender, ethnic background, highest academic qualification, and current CePA scores. There were significant differences in the perceptions of Overall Lecturer Factor based on students' previous work experience, and in the perceptions of Teaching Methodology and Relevance of Courses based on their level of English Language proficiency.